Musik Viral di Media Sosial dan Pembentukan Persepsi Politik Publik - Irniatie Wanda (PERPROMI, 2026)
This study examines the role of viral music on social media in shaping public political perceptions in the digital era. In contemporary political communication, music circulating through platforms such as TikTok, Instagram, and YouTube has evolved beyond entertainment into a persuasive medium influencing audience interpretation of political events, actors, and narratives. This research employs a mixed-method approach combining content analysis of viral political-themed music clips and survey data measuring audience perception changes. The findings indicate that viral music significantly contributes to the construction of simplified political narratives, emotional framing, and collective opinion formation. Algorithmic amplification, repetition, and participatory culture strengthen the persuasive power of music-based political messages. The study also reveals that audiences with higher exposure to viral political music demonstrate stronger affective responses and clearer political positioning compared to those with limited exposure. Music functions not only as an expressive cultural form but also as a strategic communicative instrument that shapes political meaning in digital public spheres. The research concludes that viral music plays a substantial role in influencing public political perception by merging entertainment, emotion, and algorithm-driven visibility.